2015
DOI: 10.1007/s00330-014-3573-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling DW-MRI data from primary and metastatic ovarian tumours

Abstract: ObjectivesTo assess goodness-of-fit and repeatability of mono-exponential, stretched exponential and bi-exponential models of diffusion-weighted MRI (DW-MRI) data in primary and metastatic ovarian cancer.MethodsThirty-nine primary and metastatic lesions from thirty-one patients with stage III or IV ovarian cancer were examined before and after chemotherapy using DW-MRI with ten diffusion-weightings. The data were fitted with (a) a mono-exponential model to give the apparent diffusion coefficient (ADC), (b) a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 27 publications
11
47
1
Order By: Relevance
“…The absence of a clear preference for a particular model within each grade and type of tumour indicates that the models assessed here are applicable across all tumours and the choice of model is not driven purely by characteristics of a particular tumour grade or type. The preference for a non-mono-exponential model fit for the data from these tumours is consistent with results from other studies: a study in squamous cell carcinoma of the head and neck demonstrated that the kurtosis model provided a better fit to DW-MRI data than the mono-exponential model in primary tumours and in metastatic lymph nodes [7] and a study in advanced ovarian cancer demonstrated a preference for the stretched exponential model over the mono-exponential model in the majority of primary and metastatic lesions in DW-MRI data both pre- and post-treatment [11]. Clinical studies comparing various models for DW-MRI data from prostate cancer have also demonstrated a better fit in malignant as well as benign regions using the bi-exponential model [6] or the kurtosis model [17] compared with the mono-exponential model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a clear preference for a particular model within each grade and type of tumour indicates that the models assessed here are applicable across all tumours and the choice of model is not driven purely by characteristics of a particular tumour grade or type. The preference for a non-mono-exponential model fit for the data from these tumours is consistent with results from other studies: a study in squamous cell carcinoma of the head and neck demonstrated that the kurtosis model provided a better fit to DW-MRI data than the mono-exponential model in primary tumours and in metastatic lymph nodes [7] and a study in advanced ovarian cancer demonstrated a preference for the stretched exponential model over the mono-exponential model in the majority of primary and metastatic lesions in DW-MRI data both pre- and post-treatment [11]. Clinical studies comparing various models for DW-MRI data from prostate cancer have also demonstrated a better fit in malignant as well as benign regions using the bi-exponential model [6] or the kurtosis model [17] compared with the mono-exponential model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of non-mono-exponential models provides a better description of the DW-MRI signal, and parameters derived from these models allow more detailed investigation of differences between tumour sub-types or inter-tumour heterogeneity [611] and may also provide an earlier indication of response to treatment [12, 13]. However, use of a model with a large number of additional parameters risks over-fitting the data and may be sensitive to noise characteristics of the system rather than structural properties of the tumour or normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Within different DWI models, the f and D * parameters from the IVIM model have a correlation of 0.65, which although not large indicates that they have an appreciable covariance and are difficult to confidently report (from this acquisition scheme). The very low correlation between α and DDC α in the stretched exponential model (0.083) suggests that these parameters are unique and identifiable parameters [28], associated with independent tissue properties, and thus provide more information than the simple ADC model [29]. The same is true of the pseudo-diffusion-related parameters in the IVIM model, and K in the kurtosis model, although the higher CVs observed for these may limit their utility.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the choice of the mathematical model depends on the anatomical region in the study but it is imperative to have the flexibility of using different models as this could influence repeatability. In a recent study on primary and secondary ovarian cancer, a stretched exponential model showed better repeatability over mono-exponential and biexponential models [151] . Finally, in any DW-MRI study, system-induced variability must be established using a standardized phantom as was recommended in the 2009 meeting report [5] .…”
Section: Need For Validationmentioning
confidence: 99%